THE APPLICATION OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TECHNIQUE TO TEACH READING COMPREHENSION OF DESCRIPTIVE TEXT TO THE SEVENTH GRADERS OF JUNIOR HIGH SCHOOL (RETAIN, 2014)
Abstrak Penelitian ini bertujuan untuk menggambarkan penerapan teknik Cooperative Integrated Reading and Composition (CIRC) untuk mengajar pemahaman membaca teks deskriptif untuk kelas tujuh SMP. Penelitian ini mengambil beberapa permasalahan: (1) bagaimana penerapan teknik CIRC dalam mengajar membaca teks deskriptif untuk kelas 7 SMP? (2) bagaimana hasil siswa dalam membaca teks descriptif setelah diterapkan teknik CIRC? dan (3) bagaimana tanggapan siswa terhadap teknik CIRC dalam pembelajaran membaca teks deskriptif? Penelitian ini telah membuktikan bahwa teknik Cooperative Integrated Reading dan Composition (CIRC) dapat membantu siswa dalam membaca teks deskriptif karena mereka bisa mudah untuk memahami teks. Tugas membaca siswa menunjukkan hasil yang baik setelah dianalisis dengan menggunakan Extended Reading Rubric oleh Anwar. Analisis tersebut meliputi: pembaca menunjukkan pemahaman yang akurat tentang informasi penting dalam teks dengan berfokus pada ide-ide kunci yang disajikan secara eksplisit dan implisit, pembaca menggunakan informasi dari teks untuk menafsirkan konsep yang signifikan atau membuat koneksi untuk situasi atau konteks lain secara logis melalui analisis , evaluasi, kesimpulan, atau perbandingan / kontras, pembaca menggunakan referensi yang relevan dan akurat; spesifik dan didukung sepenuhnya, dan pembaca mengintegrasikan penafsiran teks dengan dukungan berbasis teks (skor). Komponen dikelompokkan menjadi lima nilai, yaitu: sangat amat baik (100-85), sangat baik (84-70), baik (69-50), sedang (49-20) dan buruk (19-0). Penelitian ini menyimpulkan bahwa Cooperative Integrated Reading dan Composition (CIRC) memberikan efek positif untuk membantu siswa dalam membaca teks deskriptif. Hasil nilai siswa menunjukkan hasil yang baik dengan menerapkan Cooperative Integrated Reading and Composition (CIRC). Para siswa memiliki pencapaian dalam belajar membaca teks deskriptif karena sebagian besar siswa dapat mencapai standar nilai minimal. Kata kunci: membaca, teks deskriptif dan CIRC. Abstract This study is designed to describe the application of Cooperative Integrated Reading and Composition (CIRC) technique to tech reading comprehension of descriptive text to the seventh graders of Junior High School. This study composes some questions: 1.) How is the application of Cooperative Integrated Reading and Composition (CIRC) technique to teach reading comprehension in descriptive text for the 7th grade of Junior High School? 2.) How is the students’ reading ability after applying Cooperative Integrated Reading and Composition (CIRC) technique? 3.) What are the students’ responses toward their teachers’ technique in teaching reading comprehension for the 7th grade of Junior High School? This study has proved that the Cooperative Integrated Reading and Composition (CIRC) technique can help the students in reading descriptive text because they could be easy to understand the text. The students’ reading task showed good result after being analyzed by using Extended Reading Rubric by Anwar. The analyzing was including: the reader demonstrates an accurate understanding of important information in the text by focusing on the key ideas presented explicitly and implicitly, the reader uses information from the text to interpret significant concepts or make connections to other situations or contexts logically through analysis, evaluation, inference, or comparison/ contrast, the reader uses relevant and accurate references; most are specific and fully supported and the reader integrates interpretation of the text with text-based support (balanced). Those components were categorized into five scores. They are excellent (100-85), very good (84-70), good (69-50), average (49-20) and poor (19-0). This study concludes that Cooperative Integrated Reading and Composition (CIRC) give positive effect to help the students in reading descriptive text. The students’ result score showed good result by applying of Cooperative Integrated Reading and Composition (CIRC). The students had achievement in learning reading descriptive text because most of the students could achieve the standard of minimum score. Key word: reading, descriptive text and CIRC.